2019
DOI: 10.3390/coatings9060346
|View full text |Cite
|
Sign up to set email alerts
|

Surface Treatment for Improving Durability of Aluminum-Lithium Adhesive-Bonded Joints under Hot-Humid Exposure

Abstract: The performance of adhesive-bonded joints, which are being increasingly used in the aerospace and automotive industries, under hot-humid conditions remains largely unknown. The effect of surface treatments on the strength durability of aluminum-lithium (Al-Li) alloy adhesive-bonded joints under hot-humid exposure was investigated. Varied surface characteristics were achieved by different mechanical and chemical treatments; combined mechanical and phosphoric acid anodization (PAA) treatments were also used. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Surface preparation and different surface treatments were also shown by several authors to play a key role in the water sorption characteristics of an adhesive joint. 69,112,127,128 Sargent 69 determined the effect of the immersion in distilled water at 35 C on adhesive joints with aluminum substrates and phenolic and epoxy-based adhesives for over seven years. The adhesive-adherend combination was found considerably stable even with a significant water concentration, since periodic peel strength tests showed constant joint behavior and no corrosion was found on the substrate.…”
Section: Moisture Agingmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface preparation and different surface treatments were also shown by several authors to play a key role in the water sorption characteristics of an adhesive joint. 69,112,127,128 Sargent 69 determined the effect of the immersion in distilled water at 35 C on adhesive joints with aluminum substrates and phenolic and epoxy-based adhesives for over seven years. The adhesive-adherend combination was found considerably stable even with a significant water concentration, since periodic peel strength tests showed constant joint behavior and no corrosion was found on the substrate.…”
Section: Moisture Agingmentioning
confidence: 99%
“…Li et al 128 studied SLJs with aluminum-lithium substrates subjected to different surface treatments, analyzing their behavior at a humid environment at high temperature. The surfaces were treated with sandpaper, sandblasting, chemical etching and PAA.…”
Section: Moisture Agingmentioning
confidence: 99%
“…They showed that the strength of the adhesive joints depends on the type of bonded material. The moderate value of the surface roughness results in a diffusion of moisture, which contributes to the durability of the adhesive joint [28]. Thus, the surface roughening could be applied to certain optimal values, characteristic for a type of material.…”
Section: Fig 5 Example Of Adhesion Failure (Af)mentioning
confidence: 99%
“…Generally, these methods can be categorized into mechanical, chemical, electrochemical, coupling agents, etc. Figure 2 shows the surface morphologies of an Al-Li alloy after surface treatments of sandpaper abrading, sandblasting, chemical etching and phosphoric acid anodizing (PAA) [38]. The use of surface treatment methods, before lamination, can significantly influence the surface morphology, surface energy, wettability and consequently, the mechanical properties of FMLs [27,[39][40][41][42][43][44][45].…”
Section: Effects Of Cnts On the Mechanical Properties Of Fmlsmentioning
confidence: 99%
“…Surface morphologies of Al-Li alloy after surface treatments of (a) sandpaper abrading, (b) sandblasting, (c) chemical etching, and (d) PAA [38]. …”
Section: Effects Of Cnts On the Mechanical Properties Of Fmlsmentioning
confidence: 99%